Chronic Intermittent Hypoxia Induces the Long-Term Facilitation of Genioglossus Corticomotor Activity - Zou, Ying (Can Respir J, 2018)
Obstructive sleep apnea (OSA) is characterized by the repetitive collapse of the upper airway and chronic intermittent hypoxia (CIH) during sleep. It has been reported that CIH can increase the EMG activity of genioglossus in rats, which may be related to the neuromuscular compensation of OSA patients. This study aimed to explore whether CIH could induce the long-term facilitation (LTF) of genioglossus corticomotor activity. 16 rats were divided into the air group (n=8) and the CIH group (n=8). The CIH group was exposed to hypoxia for 4 weeks; the air group was subjected to air under identical experimental conditions in parallel. Transcranial magnetic stimulation (TMS) was applied every ten minutes and lasted for 1 h/day on the 1st, 3rd, 7th, 14th, 21st, and 28th days of air/CIH exposure. Genioglossus EMG was also recorded at the same time. Compared with the air group, the CIH group showed decreased TMS latency from 10 to 60 minutes on the 7th, 14th, 21st, and 28th days. The increased TMS amplitude lasting for 60 minutes was only observed on the 21st day. Genioglossus EMG activity increased only on the 28th day of CIH. We concluded that CIH could induce LTF of genioglossus corticomotor activity in rats.